2017
DOI: 10.3892/ol.2017.6712
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate suppresses cell proliferation and promotes apoptosis in Ec9706 and Eca109 esophageal carcinoma cells

Abstract: Abstract. Epigallocatechin-3-gallate (EGCG) is a component of green tea with anticancer effects that have been demonstrated in multiple types of cancer, but few reports exist concerning its effect in esophageal squamous cell carcinoma cells. The present study investigated apoptosis induced by EGCG treatment and the underlying molecular mechanisms in Eca109 and Ec9706 human esophageal squamous cell carcinoma cells. The apoptosis rate following treatment with various concentration of EGCG for 24 h was detected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 25 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…In prostate cancer cell lines, it has been observed that the EGCG-dependent reduction of the acetylated androgen receptor (AR) gene might be induced by EGCG reduction in HAT activity [65]. EGCG also acts on teleomerase, reducing its activity in different tumor types as esophageal carcinoma [230], glioma [231], cervical cancer [232], breast cancer [100], nasopharyngeal carcinoma [233], ovarian cancer [68], laryngeal squamous cell carcinoma [234], and lung cancer [235]. It has also been shown that EGCG can translocate from the cytoplasm to the nucleus where it can bind to DNA, suggesting a possible role in gene expression regulation also through the direct binding to nucleic acid [236,237].…”
Section: Egcg Epigenetic Regulationmentioning
confidence: 99%
“…In prostate cancer cell lines, it has been observed that the EGCG-dependent reduction of the acetylated androgen receptor (AR) gene might be induced by EGCG reduction in HAT activity [65]. EGCG also acts on teleomerase, reducing its activity in different tumor types as esophageal carcinoma [230], glioma [231], cervical cancer [232], breast cancer [100], nasopharyngeal carcinoma [233], ovarian cancer [68], laryngeal squamous cell carcinoma [234], and lung cancer [235]. It has also been shown that EGCG can translocate from the cytoplasm to the nucleus where it can bind to DNA, suggesting a possible role in gene expression regulation also through the direct binding to nucleic acid [236,237].…”
Section: Egcg Epigenetic Regulationmentioning
confidence: 99%
“…Therefore, further studies should focus on the mechanism of EGCG on depolymerizing cellular microtubule. In addition, EGCG can inhibit telomerase in breast cancer [ 117 ], esophageal carcinoma [ 118 ], endocervical cells and ectocervical cells [ 42 ], but shows much milder cytotoxic effects in cervical cancer cells [ 119 ]. The activity of telomerase is related to DNA methylation [ 120 ], and thus whether EGCG can inhibit telomerase activity through reducing DNA methylation is a promising research project.…”
Section: Further Suggestionsmentioning
confidence: 99%
“…EGCG is a naturally occurring polyphenol from the catechin group found in tea (green, white and black), fruits (apples and plums), vegetables (onions and carobs) and nuts (hazelnuts and pecans). EGCG possibly induces apoptosis and telomerase inhibition activity, and provokes mitochondrial membrane potential and caspase-3 expression in various cancer cells [ 215 , 216 , 217 ]. In addition, EGCG has down-regulated the mRNA and protein expression of hTERT and c-Myc protein [ 218 ].…”
Section: Telomerase Inhibitors From Natural Productsmentioning
confidence: 99%
“…Low cytotoxic dose EGCG and (−)-epigallocatechin (EGC) have suppressed hTERT expression on reporter system and hTERT mRNA level in various cancers [ 213 , 214 ]. Liu et al [ 217 ] reported that EGCG induces apoptosis by down-regulating hTERT and B cell lymphoma 2 (Bcl-2), arresting cells in both G2/M and S phase and promoting DNA damage response specifically in ovarian cancer cell lines.…”
Section: Telomerase Inhibitors From Natural Productsmentioning
confidence: 99%